Recommendation for the Use of Regional Tourist Resources by the Example of the Resort City of Sochi, Russia - KATAEVA, Valentina; FOMICHEVA, Tatiana; SULYAGINA, Julia; KUVSHINOVA, Julia; EVSTRATOVA, Tatiana; MOSKVITIN, Gennady (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.v10.1(33).24, 2019)
Issues related to the measures aimed to improve the competitiveness of tourist destinations have currently become most urgent. The number of competing tourist destinations in Russia and worldwide is on the rise, leading to tough competition among market participants that feel necessary to improve the efficiency of management in the tourism industry. Tourism development in the regions can be considered as a factor of regional socio-economic development. The research contains recommendations on the management of tourist resources, and measures aimed to enhance the region’s tourist attractiveness by the example of the resort city of Sochi.